Cultivating Responsible Character Through Pancasila and Citizenship Education Learning (A Descriptive Study of Class X Learning at SMA 1 Aek Natas) - Tegar Ramadhana Damanik; Siti Zahara Saragih; Mila Nirmala Sari Hasibuan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
In learning, various problems that are often encountered include students lacking a sense of responsibility for learning in Pancasila and Citizenship Education learning. From the results of observations and interviews, researchers found several problems related to the character of student responsibility, namely when the teacher gives assignments, students are unable to submit the assignments given by the teacher on time, when doing assignments, students do it by looking at their friends' work. The purpose of the study was to determine the instilling of the character of responsibility through Pancasila and Citizenship Education learning. This study was conducted in class X at SMA 1 Aek Natas. The research period was 6 months, starting from November 2025 to April 2026. The research method used was a descriptive method with a qualitative approach. This study used observation, interview, and documentation data collection techniques. The instruments in this study were using observation guidelines, interview guidelines, and documentation. Data examination in this study was carried out by Extending Observations, increasing perseverance, triangulation tests and member checking data from various sources with various techniques. The results of the study showed that, (1) instilling the character of responsibility in students, namely teachers integrate character values, especially the character of responsibility into the material being taught. The instilling of the character of responsibility is not only done in the classroom when lessons are taking place, but is also done outside the classroom, namely through various habits, (2) supporting factors, namely teachers being role models for students, rules that must be obeyed, and the existence of Standard Operating Procedures. Inhibiting factors are the absence of a book connecting teachers with parents, (3) the instilling of the character of responsibility through learning is done using lecture methods, discussions, questions and answers, assignments and using strategies (CTL).